JASON WALKER’S MOTIVATION TO SURVIVE IN BRANDON MULL’S NOVEL SERIES BEYONDERS: A WORLD WITHOUT HEROES - Masdin, M. Wahyuddin; Nurindah, Nurindah; Sapan, Yulius Tandi (Journal of Teaching of English, 2020)
Literature is a written work that have intellectual and imaginative ideas with a neat and organized structure. Novel as a kind of literary works is a piece of writing in form of prose which has complex attribute such as complicated plots, various settings, and a great variety of characters.One of the best fantasy works is Beyonders series, written by Brandon Mull.Beyonders: A World Without Heroes is the first of Beyonders trilogy series. The story of Beyonders: A World Without Heroes novel is about a thirteen years old boy named Jason Walker who trying to find a way to go back to his world. From Beyonders: A World Without Heroes novel, things that stand out are the story of a struggle to survive and find the way to go back home.Therefore, one of the particular elements to build the story in the novel is motivation of the major character.Motivation helps to achieve something that can make a better circumstance, we will not be able to achieve anything if we do not have any desire to achieve it.This study aimed to analyze Jason Walker’s motivation to survive in Brandon Mull’s novel series Beyonders: A World Without Heroes. This study used Personal Construct Theory (PCT) which classified emotions to analyze Walker’s motivation to survive as to which emotions caused Walker to be motivated to survive. This study found that Walker’s motivation in real world is his interest towards animals was what motivated Walker to study in zoology major. Trapped in unreal world made Walker motivated to survive to find a way home and  as  setting  and  conflict  influenced,  Walker’s  motivation  has grown to save Lyrian from Maldor. By using Kelly’s Personal Construct Theory (PCT), this study found that anxiety on why Walker was stranded in unreal world, guilt of involving Lyrian’s people and did not want to make his family and friends worried about him, threat from Maldor